Natural product inspired organic synthesis: enantiopure heterocycles modelled on pramanicin - Tan, S (2014)
This thesis is concerned with the synthesis of chiral pyrrolidinone scaffolds as mimics of the natural product pramanicin, and the evaluation of their antibacterial properties for use towards the development of potential novel antibacterial lead compounds. Chapter 1 discusses the urgency of the antibiotic resistance problem as well as the current lack of new antibiotics in the drug pipeline. This dearth of new antibacterials is partly attributed to the combinatorial libraries used in the screening process which occupies a limited chemical space. By applying the natural product-inspired paradigm, it is hypothesised that a drug discovery process with a starting point based on a natural product, possessing intrinsic antibacterial properties, may provide insights to a novel class of antibacterials. Chapter 2 describes the synthesis of three different scaffolds of oxygenated pyrrolidinones via a common bicyclic intermediate synthesised from L-pyroglutamic acid. The use of a mild and facile epoxidation condition utilising H2O2/tertiary amine afforded the epoxypyrrolidinones. α-Hydroxylation with “Davis oxaziridine” and a Ru-mediated dihydroxylation gave 2-hydroxypyrrolidinones and 2,3-dihydroxypyrrolidinones respectively. In all cases, a pendant Weinreb amide was used to introduce a variety of side-chains onto the parent pyrrolidinones. The enantioselective oxygenation of these scaffolds was accomplished as a result of the chiral [3.3.0] bicyclic intermediate. Chapter 3 describes the attempted synthesis of oxygenated pyrrolidinones via tetramic acids. Although progress was thwarted by synthetic challenges discussed therein, a series of tetramic acids was synthesised. A synthetic sequence to install a 3-acyl moiety onto the parent tetramic acid core was accomplished via an O-acyl/C-acyl rearrangement using a series of carboxylic acids in the presence of excess DMAP. The use of a 3-acyltetramic acid with a pendant phosphorane permits a general synthetic route, compatible with a wide range of aldehydes, towards 3-enoyltetramic acids via Horner-Wadsworth-Emmons olefination. These tetramic acids are mimics of another class of bactericidal natural products which nonetheless allows the natural product-inspired paradigm to be investigated. Finally, an analysis of the antibacterial properties of the synthesised compounds is discussed in Chapter 4. A cellular hole-plate bioassay with E. coli and S. aureus was chosen to provide a rapid assessment for active compounds. A correlation between the physicochemical properties and the observed activities of these active compounds suggested possible chemical modifications which could be undertaken in the future to improve their activities.